2007
DOI: 10.1002/bjs.5790
|View full text |Cite
|
Sign up to set email alerts
|

Tumour cell dissemination following endoscopic stent insertion

Abstract: Endoscopic insertion of colonic stents but not staging colonoscopy results in increased levels of CK20 mRNA in the peripheral circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
141
3
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(152 citation statements)
references
References 13 publications
5
141
3
3
Order By: Relevance
“…Although considered at low risk, 10e20% of patients with colorectal cancer stage I and II ultimately will develop recurrent disease. 10,11 It is in this population that prognostic markers may identify a subgroup of patients who are at a higher risk for disease relapse and who may also benefit from adjuvant therapy, especially from antitumoral agents with low systemic toxicity such as monoclonal antibodies, which have also proven to be effective against dormant tumor cells. 6,7 In this regard, there are several studies that have demonstrated that tumor cell detection is clearly related to an early relapse and decreased survival of the respective patients.…”
Section: Prognostic Factors and Management Of Colorectal Cancermentioning
confidence: 99%
“…Although considered at low risk, 10e20% of patients with colorectal cancer stage I and II ultimately will develop recurrent disease. 10,11 It is in this population that prognostic markers may identify a subgroup of patients who are at a higher risk for disease relapse and who may also benefit from adjuvant therapy, especially from antitumoral agents with low systemic toxicity such as monoclonal antibodies, which have also proven to be effective against dormant tumor cells. 6,7 In this regard, there are several studies that have demonstrated that tumor cell detection is clearly related to an early relapse and decreased survival of the respective patients.…”
Section: Prognostic Factors and Management Of Colorectal Cancermentioning
confidence: 99%
“…Theoretically, enforced radical dilatation by a stent could not only increase the risk of perforation, but tumor manipulation can result in cancer cell spread into the surrounding lymphatic vessels and peripheral bloodstream (4,21,22). Accordingly, in the present study, it was found that a markedly increased number of v-CTCs detected by a novel method, TelomeScanF35 (13), was found in patients' circulation after completion of endoscopic stent insertion.…”
Section: Discussionmentioning
confidence: 49%
“…Early studies suggested an oncological compromise associated with tumour perforation or tumour cell dislodgement during SEMS insertion resulting in seeding of malignant cells. 13 Manipulation of the tumour by the shearing forces of endoscopy and colonic insufflation is thought to disseminate tumour cells locally and into the circulation. 43 Three RCTs have investigated long-term oncological outcome, all the sample sizes were small (15-26 patients in the SEMS groups), and found increased disease recurrence in the SEMS groups.…”
Section: Sems As a Bridge To Elective Surgerymentioning
confidence: 99%
“…11 Importantly, in the latter scenario, concern has been raised following analysis of RCT follow-up data regarding the oncological impact of SEMS use. [12][13][14] It is only recently that there has been some clarity as to the most appropriate clinical indications for SEMS in malignant colonic obstruction.…”
Section: Introductionmentioning
confidence: 99%